Media Representations and Ageing: The Influence of Bollywood on the Upper Economic Class in Urban Mumbai and Implications for Media Literacy - Madhukullya, Samikshya; Gupta, Sandeep (CV. Bimbingan Belajar Assyfa, 2025)
Mumbai's urban upper economic class faces unique pressures to maintain youthfulness, shaped by pervasive societal norms and the influential portrayals of ageing in Bollywood media. This study aims to evaluate how Bollywood's representations impact perceptions of ageing among Mumbai's affluent, and to explore the implications for media literacy and educational strategies. Employing a quantitative survey approach, data were collected from 32 upper-class residents of Mumbai using Google Forms and analyzed with SPSS to assess attitudes toward ageing, the influence of media, and gendered expectations. The findings reveal that Bollywood's youth-centric narratives significantly contribute to negative perceptions of ageing, reinforcing ageist stereotypes and intensifying the desire to appear youthful, with notable differences between male and female respondents. These results underscore the urgent need for inclusive and diverse media representations, as well as the integration of media literacy interventions in educational and community settings to foster critical engagement with age-related stereotypes. The study concludes that promoting media literacy and age-inclusive content can play a pivotal role in challenging societal biases, supporting intergenerational understanding, and informing policy and curriculum development in urban India.